Organ-Specific Protective Role of NKT Cells in Virus-Induced Inflammatory Demyelination and Myocarditis Depends on Mouse Strain - Kawai, Eiichiro (J Neuroimmunol, 2014)
Theiler’s murine encephalomyelitis virus (TMEV) can induce demyelination or myocarditis in susceptible mouse strains. A deficiency of NKT cells exacerbated TMEV-induced demyelinating disease (TMEV-IDD) in SJL/J and BALB/c mice. In C57BL/6 background, however, NKT-cell-deficient Jαt 18 KO mice remained as resistant to TMEV-IDD as wild-type mice. Echocardiography and histology showed that Jα18 KO mice developed more severe myocarditis (greater T cell infiltration and fibrosis) than wild-type mice, suggesting a protective role of NKT cells in myocarditis in C57BL/6 mice. Jα18 KO mice had higher cardiac viral RNA and anti-viral antibody titers, but had lower lymphoproliferation and IL-4 and IL-10 production.